Analysis of Empowerment, Organizational Commitment and Competence in Improving Employee Performance: Study on the Regional Revenue Agency of Southeast Sulawesi Province - Mekou, Asdiana; Samdin, Samdin; Sabilalo, Mahmudin A. (Journal of Business Management and Economic Development, 2024)
This research is aimed at investigating the influence of employee empowerment, organizational commitment, and competence on enhancing employee performance at the Regional Revenue Authority of Southeast Sulawesi Province. Utilizing a qualitative approach and the Interactive Analysis Model from Miles and Huberman, this study analyzes data from six informants to explore how these three factors individually and collectively contribute to employee performance. The findings indicate that employee empowerment through authority delegation and capability development significantly contributes to performance enhancement. Organizational commitment, influenced by organizational justice and recognition of performance, is also proven to enhance employee performance. Meanwhile, employee competence, encompassing knowledge, skills, and attitudes, is found as a critical factor supporting work effectiveness and efficiency. These findings offer valuable insights for the development of human resource management strategies in the public sector, particularly in efforts to enhance organizational performance. This study contributes to the literature by identifying and analyzing key factors influencing employee performance in the local government sector and suggesting practical applications of the research findings for policy development and human resource management practices at the Regional Revenue Authority.